Model Perilaku Perpindahan Merek Pada Beauty Clinic - muji rahayu, tri septin; Lusiana Suprapti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to determine the effect of independent variables are which post-consumption dissatisfaction, switching costs and word of mouth on towards brand switching. Data collection techniques this research used is purposive sampling metodh with 100 respondents. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that the variables of post-consumer dissatisfaction, switching cost and word of mouth simultaneously have a positive and significant effect on the brand's switching decision to move to the Reta Beauty Clinic. Post-consumption dissatisfaction, switching cost variable partially has no effect on brand switching decisions. Word of mouth variabels partially have a positive and significant effect on brand switching decisions.